Blockchain and Cryptocurrency (Legal Challenges in Implementing Smart Contracts) - Ali Bukhtiar; Hafiz Abdul Rehman Saleem; Asif Iqbal; Muhammad Sohaib Younas; Atif Hassan (Research Journal of Psychology, 2025)
The development of blockchain technology and its affiliated cryptocurrencies quickly changed the outlook for numerous industries; the most recent, however is that of the smart contract, a self-executing digital agreement whose terms of contract are followed by automatic execution on specific conditions. Yet, despite the huge potential to transform the way transactions are conducted, implementing smart contracts within blockchain and cryptocurrency systems faces a host of legal issues. The research discussed the core legal issues of smart contracts, primarily being a lack of clarity concerning the regulatory framework, lack of clear regulation of enforcement in the traditional legal system, and issues with dispute and accountability. In the same context, the article takes the reader on a journey about the intricacies involved in understanding party intent when using smart contracts. The coding of the contracts might not always capture all the nuances within an agreement. Moreover, certain issues such as the anonymity of a blockchain system, further add the complexity to define the parties at fault in breach or fraud circumstances. This study aims at understanding the junction of law and technology, to identify key barriers that need to be addressed so that smart contracts can be appropriately used in the blockchain and cryptocurrency ecosystem. This research will deliver findings on the adaptation of new digital technologies with legal frameworks for accommodating these newer digital technologies. Recommendations will then be given on how to overcome the problems that are present with the current technology.